The Role of Ning Influencer in Realizing Religious Moderation on Social Media - Nafisah, Dhurrotun (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
This article discusses the preaching of ning influencers in spreading the value of religious moderation on social media. This research is devoted to Ning Imaz's da'wah content on the YouTube platform. The significance of this research is established through two arguments. First, the Islamic boarding school community has an important role in the dynamics of religious life in Indonesia. Second, the existence of ning Islamic boarding schools is vital in the contestation of da'wah on social media. Islamic boarding schools, as institutions that have legitimacy in Islamic scholarship, need to capture the collective understanding that exists in the wider community regarding the patronage of religious figures who tend to be extreme and intolerant. The method used in this research is digital ethnography. The actualization of the value of religious moderation in the form of video content is a means of correcting religious misunderstandings that are spreading on social media.